Metformin protects against pericyte apoptosis and promotes neurogenesis through suppressing JNK p38 MAPK signalling activation in ischemia/reperfusion injury. (13th July 2022) - Liu, Chang; Zhang, Di; Lu, Zhengfang; Man, Jiang; Zhang, Zhen; Fu, Xiaojuan; Cui, Kefei; Wang, Jianping
Graphical abstract: Highlights: Metformin inhibited pericytes apoptosis contributing to promoting SVZ neurogenesis and neurologic outcome in tMCAO mice. Metformin supressed JNK p38 MAPK signalling activation in tMCAO mice which inhibited pericytes apoptosis. Anisomycin abolished neuroprotective effects of Metformin through activating JNK p38 MAPK signalling. Abstract: Metformin (MET) has been the subject of many classic studies in possessing antiapoptotic, anti-inflammatory, antioxidation activities and antiviral. Recently investigators have examined the anti-apoptosis effects of MET in acute myocardial infarction and Intracerebral hemorrhage, but very little is currently known about how it regulates ischemic stroke-induced pericytes apoptosis and neural stem cells (NSCs) proliferation. The present research explored the potential neuroprotective mechanisms of MET using transient middle cerebral artery occlusion(tMCAO) mice. The experimental work presented that tMCAO mice treated by metformin had better neurologic outcomes on days 1, 3, and 7 after operation, and alleviated blood–brain barrier (BBB) destruction, brain water content and infarct volume on 72 h after surgery. The data showed that MET alleviated BBB disruption by reducing PDGFRβ/ matrix metalloproteinase-9 (MMP9) positive cells, relieving zonula occludens-1 (ZO-1) drop away and increasing pericyte coverage through remarkably reducing the percentage of PDGFRβ/caspase-3 positive cells. In addition, MET induced antiapoptotic activity followed by downregulating cleaved caspase-3 and Bax expression. Moreover, JNK signaling pathway has been proved to be pivotal in mediating apoptosis in cerebral ischemia/reperfusion (I/R) injury. The results of this research illustrated that MET treatment downregulated the levels of phosphorylated JNK and P38 in vivo, however the use of JNK activator anisomycin (ANI) could reverse the neuroprotection effect of MET, demonstrating that the JNK pathway is associated with the anti-apoptosis mechanisms of MET. Finally, metformin remarkably increased the percentage of BrdU/DCX-positive cells in subventricular zone (SVZ) and up-regulated BDNF、VEGF and NGF expression after ischemia/reperfusion(I/R) injury on day 7. Our data illustrated that metformin provides an effective therapy for I/R injury.